PENGARUH PROFESIONALISME, PENGALAMAN AUDITOR, TIME PRESSURE DAN AUDIT FEE TERHADAP KUALITAS AUDIT - Muhammad Rhafli Qhatammi (2023)
This research is a quantitative study that aims is to determine professionalism, auditor experience, time pressure, and audit fees on audit quality. This study uses primary data from the population, namely the Public Accounting Firm (KAP) in South Jakarta. The observation data for this research amounted to 116 respondents. The data analysis method was carried out using Structural Equation Modeling (SEM), which is usually called partial least squares (PLS) as a data analysis method. The data analysis method is carried out using Structural Equation Modeling (SEM), which is usually called partial least squares (PLS) as a data analysis method. The results of hypothesis testing show that (1) Professionalism has a positive effect on audit quality, ( 2) Auditor experience has a positive effect on audit quality, (3) Time Pressure has a positive effect on audit quality, (4) Audit Fees has a negative effect on audit quality.